Christian faith, philosophy & international relations: the lamb and the wolf - Polinder, Simon; Buijs, Govert J. (Brill, 2020)
"International relations are in constant turbulence. Globalisation, the rise and fall of superpowers, the fragilisation of the EU, trade wars, real wars, terrorism, persecution, new nationalism and identity politics, climate change, are just a few of the recent disturbing developments. How can international issues be understood and addressed from a Christian faith perspective? In this book answers are presented from various Christian traditions: Neo-calvinism, Catholic social teaching, critical theory and Christian realism. The volume offers fundamental theological and Christian philosophical perspectives on international relations and global challenges, case studies about inspiring Christian leaders such as Robert Schuman, Dag Hammarskjöld, Abraham Kuyper and prophetic critiques of supranational issues"--
Includes bibliographical references and index
Keywords: Aufsatzsammlung; Anthropogene Klimaänderung; Handelskrieg; Globalisierung; Internationale Politik; Christliche Philosophie